PROSES PEMBEKUAN IKAN KATAMBA (Lethrinus lentjan) PRODUK WGGS (WHOLE GILLED GUTTED SCALED) - Habibatun Naimah; Ika Junianingsih (Faculty of Science and Technology University Ibrahimy, 2014)
The purpose of this study was to determine the clotting process fish products katamba lethrinus lentjan gilled Whole Gutted Scaled Wggs (WGGS) conducted in PT Sulindo (Success Lautan Indonesia) Mayangan Probolinggo, East Java. The study was conducted in date of February 2013. The method used was a survey, the data obtained by observation, interviews, participation, and documentation, and then performed a descriptive analysis. Stages in the process of freezing the fish katamba product WGGS are as follows: raw material receiving, sorting I, weighing I, leaching I, disposal scales, washing, removal of gills and entrails, washing III, sorting II, weighing II, leaching IV, the preparation in the long pan, freezing, metal detecting, weighing 3, glazing, packaging and labeling, and storage.